Impact of successful pediatric ureteropelvic junction obstruction surgery on urinary HIP/PAP and BD-1 levels. Issue 5 (October 2020) - Gupta, Sudipti; Nicassio, Lauren; Junquera, Guillermo Yepes; Jackson, Ashley R.; Fuchs, Molly; McLeod, Daryl; Alpert, Seth; Jayanthi, Venkata R.; DaJusta, Daniel; McHugh, Kirk M.; Becknell, Brian; Ching, Christina B.
Summary: Introduction: In the pediatric patient whose ureteropelvic junction obstruction (UPJO) is not always symptomatic, imaging is the most common means of detecting surgical success. There is interest, however, in other means of post-operative monitoring. A panel of antimicrobial peptides (AMPs) has been previously found to be elevated in UPJO, but the impact of surgical correction on these AMPs is unknown. Objective: To determine if elevated levels of candidate urinary AMP biomarkers of urinary tract obstruction decrease following UPJO repair. Study design: Pediatric patients undergoing surgical correction of an UPJO were recruited for participation. Bladder urine from uninfected consenting/assenting patients was collected immediately prior to surgery and then at least 6 months afterward. Based on prior studies demonstrating significant elevation of beta defensin 1 (BD-1), hepatocarcinoma-intestine-pancreas/pancreatitis-associated protein (HIP/PAP), cathelicidin (LL-37), and neutrophil gelatinase-associated lipocalin (NGAL) in patients with UPJO versus control patients, we performed enzyme-linked immunosorbent assays on these four AMPs to compare their expression before and after surgical intervention. If found to significantly decrease, AMP levels were compared to healthy controls. AMP levels were normalized to urine creatinine. Results were analyzed with paired t test or Wilcoxon test using Graphpad software. Correlation was calculated using Pearson or Spearman correlation. A p-value of <0.05 was considered significant. Results: 13 UPJO patients were included in this study; 9 were male (69%). Age at surgery was a median of 4.3 years (average 6.1, range 0.4–18.4 years). Follow-up urine samples were collected a median of 27.4 months after surgery (average 27.4; range 7.8–45.3 months). All 13 patients had clinical improvement and/or signs of improved hydronephrosis on post-operative imaging. HIP/PAP and BD-1 significantly decreased in post-surgical samples compared to pre-surgical samples (p = 0.02 and 0.01, respectively); NGAL and LL-37 did not significantly change. Overall, HIP/PAP decreased in 12 patients (92%) and BD-1 decreased in 11 patients (85%). BD-1 levels after successful repair were not different from healthy controls (p = 0.06). Discussion: Urinary biomarkers of obstruction should detect significant obstructive pathology as well as reflect its resolution. This would enable their use in post-operative monitoring and augment current methods of determining successful surgical outcome through imaging. Conclusions: The AMPs HIP/PAP and BD-1 are significantly elevated in UPJO but then significantly decrease after pyeloplasty, with BD-1 returning to healthy control levels. As a result, these AMPs could serve as markers of successful surgical intervention. Summary Figure Urinary markers before (Pre) and after (Post) successful surgical correction. HIP/PAP and BD-1 expression significantly decrease upon paired analysis after successful surgical correction for ureteropelvic junction obstruction (∗p = 0.0215; ∗∗p = 0.0052). Summary Figure